When the Eel Meets Dams: Larger Dams’ Long-Term Impacts on Anguilla anguilla (L., 1758) - Podda, Cinzia; Palmas, Francesco; Pusceddu, Antonio; Sabatini, Andrea (Frontiers in Environmental Science, 2022)
Diadromous fish, like the European eel Anguilla anguilla (L., 1758), are highly threatened by dams that disrupt river connectivity, consequently impeding fish movements to reach feeding and spawning habitats. In this study, variation in eel occurrence between a historical period (1940–1970) and recent data (2016–2020) was assessed throughout the Sardinian rivers’ network (more than 450 sites). Using Boosted Regression Trees (BRT) we investigated relationships between eel’s occurrence and a set of spatial and temporal environmental variables including a set of dams’ construction features for each period. An overall decrease by 65% of eel’s occurrence was noticed during the ca. 80-years period under scrutiny. Considering a subset (105 and 88 sites for the historical and the recent period, respectively) characterized by the presence of larger dams (height >15 m), eel’s occurrence dropped by 85%. Conversely, eel’s occurrence dropped only by ca. 44% in dam-free sites. During the historical period, eel’s occurrence was mostly affected by time since the initial habitat fragmentation, flow, distance to dams, connectivity, and dams’ height. In the most recent period, eel’s occurrence is mostly affected by dams’ building year, dam-to-sea distance, and, again, dams’ height. Results pinpoint that dams’ construction features and the time from their construction have significant negative effects on eel’s occurrence. Addition of future effective eel restoration practices, apart any other adverse environmental stressor, must consider dams’ removal, wherever socially sustainable or alternatively, the modification of construction features of dams (like excessive height) and the addition of fish ladders.